2021
DOI: 10.1038/s41467-021-24728-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of topological Z2 exciton-polaritons in transition metal dichalcogenide monolayers

Abstract: The rise of quantum science and technologies motivates photonics research to seek new platforms with strong light-matter interactions to facilitate quantum behaviors at moderate light intensities. Topological polaritons (TPs) offer an ideal platform in this context, with unique properties stemming from resilient topological states of light strongly coupled with matter. Here we explore polaritonic metasurfaces based on 2D transition metal dichalcogenides (TMDs) as a promising platform for topological polaritoni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 87 publications
2
45
0
Order By: Relevance
“…These quasiparticles combine the properties of their parental photon and matter components and, thereby, provide an ideal platform to study quantum many-body physics, including Bose-Einstein condensates 1 , superfluidity 2 , and Berezinskii-Kosterlitz-Thouless transition 3 . Motivated by the recent rapid progress in topological band theory [4][5][6] , there has been of great interest in applying it to polaritonic systems and exploring novel topological phenomena intrinsic to exciton-polaritons [7][8][9][10][11][12][13] . For example, in contrast to photons that rarely interact with each other, exciton-polaritons exhibit strong nonlinearities through exciton-exciton interactions [14][15][16] , allowing for the study of nonlinear and interacting topological phenomena 6 .…”
Section: Introductionmentioning
confidence: 99%
“…These quasiparticles combine the properties of their parental photon and matter components and, thereby, provide an ideal platform to study quantum many-body physics, including Bose-Einstein condensates 1 , superfluidity 2 , and Berezinskii-Kosterlitz-Thouless transition 3 . Motivated by the recent rapid progress in topological band theory [4][5][6] , there has been of great interest in applying it to polaritonic systems and exploring novel topological phenomena intrinsic to exciton-polaritons [7][8][9][10][11][12][13] . For example, in contrast to photons that rarely interact with each other, exciton-polaritons exhibit strong nonlinearities through exciton-exciton interactions [14][15][16] , allowing for the study of nonlinear and interacting topological phenomena 6 .…”
Section: Introductionmentioning
confidence: 99%
“…This opens new realms for topological multiphysics, where topological phases can be transferred from one type of physical domain to another or emerge as the result of multiphysics interactions ( 14 16 ). Recent work has shown that interactions of light with excitons may lead to the formation of topological exciton-polaritons ( 17 20 ).…”
mentioning
confidence: 99%
“…The addition of the hBN layer on top of the metasurface leads to coupling between photonic and phononic modes, giving rise to the formation of hybrid polaritonic states. The condition of strong coupling, required for the observation of topological phonon-polaritons ( 20 ), can be achieved when the hBN thickness exceeds ~5 nm. From this point forward, we consider the case of the 15-nm-thick hBN.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the crucial role played by spin-momentum locking in integrated quantum optical systems [2], our elucidation of the mechanism and its relation to the near-field will undoubtedly renew the vision of the corresponding scattering process. This is important in the current applicative perspectives discussed currently in the context of optovalleytronic systems [39], non-linear hybrid metasurfaces [40], and topology-based high-resolution sensors [41].…”
mentioning
confidence: 99%